Poly-ε-caprolactone/chitosan/whitlockite electrospun bionic membrane conjugated with an E7 peptide for bone regeneration - Guangzi Chen; Tao Xu; Ran Gao; Wenbin Liu; Weigang Li; Delu Zeng; Jian Li; Xuan Fang; Gaohong Sheng; Hongqi Zhao; Chaoxu Liu (Stem Cell Research & Therapy)
Abstract Background Periosteum plays an important role in bone defect repair due to its rich vascular network and cells. However, natural periosteum is difficult to meet clinical requirements due to its low availability. Therefore, it is necessary to develop a tissue engineering strategy of biomimetic periosteum for bone defect repair. Methods Poly-ε-caprolactone/chitosan/Whitlockite electrospun bionic membrane (PCL/CS/WH) was prepared using electrospinning technology, then it was conjugated with an E7 peptide as PCL/CS/WH/E7 bionic membrane. The physical properties of the membranes were evaluated by TEM, FTIR and tensile strength testing. In vitro, LIVE/DEAD staining and Cell Counting Kit-8 assay of bone marrow mesenchymal stem cells (BMSCs) and Endothelial progenitor cells (EPCs) are used to assess the biocompatibility of bionic membranes. Matrigel was applied to evaluate the ability of the different composite nanofibers samples to promote angiogenesis. Mineralized nodule and collagen formation in the BMSCs was detected by alizarin red staining and sirius red staining respectively. The expression of osteogenesis related genes and angiogenesis associated genes were detected using quantitative real-time polymerase chain reaction (qRT-PCR). In vivo, the ability of PCL/CS/WH/E7 membrane to promote bone regeneration and angiogenesis was assessed by Micro-CT and associated staining. Result The addition of chitosan (CS) and E7 peptide (E7) enhanced the hydrophilicity and cytocompatibility of pure PCL membranes. Additionally, CS, E7 and Mg2+ released from Whitlockite (WH) had a synergistic effect to promote angiogenesis and osteogenic differentiation. Three weeks after implantation, the membrane successfully bridged the bone defect and significantly promoted the formation of new bone and blood vessels. Conclusion The PCL/CS/WH/E7 membrane to achieve efficient repair of bone tissue and enriches clinical solutions for the treatment of critical bone defects.